Sliding‐slab three‐dimensional TSE imaging with a spiral‐In/Out readout. Issue 2 (7th March 2015) - Li, Zhiqiang; Wang, Dinghui; Robison, Ryan K.; Zwart, Nicholas R.; Schär, Michael; Karis, John P.; Pipe, James G.
Abstract : Purpose: T2 ‐weighted imaging is of great diagnostic value in neuroimaging. Three‐dimensional (3D) Cartesian turbo spin echo (TSE) scans provide high signal‐to‐noise ratio (SNR) and contiguous slice coverage. The purpose of this preliminary work is to implement a novel 3D spiral TSE technique with image quality comparable to 2D/3D Cartesian TSE. Methods: The proposed technique uses multislab 3D TSE imaging. To mitigate the slice boundary artifacts, a sliding‐slab method is extended to spiral imaging. A spiral‐in/out readout is adopted to minimize the artifacts that may be present with the conventional spiral‐out readout. Phase errors induced by B0 eddy currents are measured and compensated to allow for the combination of the spiral‐in and spiral‐out images. A nonuniform slice encoding scheme is used to reduce the truncation artifacts while preserving the SNR performance. Results: Preliminary results show that each of the individual measures contributes to the overall performance, and the image quality of the results obtained with the proposed technique is, in general, comparable to that of 2D or 3D Cartesian TSE. Conclusion: 3D sliding‐slab TSE with a spiral‐in/out readout provides good‐quality T2 ‐weighted images, and, therefore, may become a promising alternative to Cartesian TSE. Magn Reson Med 75:729–738, 2016. © 2015 Wiley Periodicals, Inc.